2019
DOI: 10.1073/pnas.1814889116
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of trabecular meshwork stiffness in a corticosteroid-induced ocular hypertensive mouse model

Abstract: SignificanceGlaucoma is the leading cause of irreversible blindness worldwide. The primary and only modifiable risk factor for the development of glaucoma is elevated intraocular pressure (IOP), and lowering IOP effectively slows glaucomatous disease progression. Unfortunately, the majority of available treatments do not target, or intentionally bypass, the diseased and stiffened glaucomatous outflow tissues responsible for IOP elevation. We recently established that conventional outflow tissue stiffness refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
131
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(146 citation statements)
references
References 53 publications
13
131
2
Order By: Relevance
“…Figure 4n shows an average reduction of 72% at +10 mm Hg and 26% reduction at +5 mm Hg. As reported by Li et al, 25 the SC size reduces roughly 80% at 20 mm Hg and 37% at 15 mm Hg. Li et al 25 did not set the IOP levels relative to baseline IOP but rather at absolute values.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Figure 4n shows an average reduction of 72% at +10 mm Hg and 26% reduction at +5 mm Hg. As reported by Li et al, 25 the SC size reduces roughly 80% at 20 mm Hg and 37% at 15 mm Hg. Li et al 25 did not set the IOP levels relative to baseline IOP but rather at absolute values.…”
Section: Discussionsupporting
confidence: 71%
“…As reported by Li et al, 25 the SC size reduces roughly 80% at 20 mm Hg and 37% at 15 mm Hg. Li et al 25 did not set the IOP levels relative to baseline IOP but rather at absolute values. Regardless, the values obtained are comparable to the degree of collapse that we observed.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Several studies found that Rho-kinase inhibitors Y-27632, Y-39983, HA-1077, and H-1152, could increase outflow and decrease IOP by altering the TM cytoskeleton [8,[18][19][20][21] . Stress fibers can contract [22] and increase stiffness [23,24] leading to decreased outflow in primary open-angle glaucoma [25] and also in glucocorticoid-induced glaucoma [26] . In our study, pigment dispersion caused a marked increase in stress fibers and IOP but then dropped to baseline after K-115 treatment.…”
Section: Discussionmentioning
confidence: 99%